2020
DOI: 10.3390/molecules25030478
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Evaluation of the Protective Effects of Hesperidin in Lipopolysaccharide-Induced Inflammation and Cytotoxicity of Cell

Abstract: (1) Background: Plant flavonoids are efficient in preventing and treating various diseases. This study aimed to evaluate the ability of hesperidin, a flavonoid found in citrus fruits, in inhibiting lipopolysaccharide (LPS) induced inflammation, which induced lethal toxicity in vivo, and to evaluate its importance as an antitumor agent in breast cancer. The in vivo experiments revealed the protective effects of hesperidin against the negative LPS effects on the liver and spleen of male mice. (2) Methods: In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
(38 reference statements)
2
18
0
Order By: Relevance
“…The study suggests that this beneficial effect is due to hesperidin. Various in vivo experiments revealed the protective effects of hesperidin against the inflammation produced by lipopolysaccharide (LPS) in liver and spleen [106].…”
Section: Other Useful Effectsmentioning
confidence: 99%
“…The study suggests that this beneficial effect is due to hesperidin. Various in vivo experiments revealed the protective effects of hesperidin against the inflammation produced by lipopolysaccharide (LPS) in liver and spleen [106].…”
Section: Other Useful Effectsmentioning
confidence: 99%
“…In addition, combination with hesperidin could potentially prevent the resistance of MCF-7 to doxorubicin treatment in breast cancers [ 29 ]. Even a single usage of hesperidin was shown to moderately reduce the colony formation of MCF-7 cells [ 30 ]. In accordance with previous reports regarding hesperidin, our findings demonstrated that hesperidin along with chlorogenic acid prominently enhanced the toxicity against MCF-7, but was less harmful to normal breast cells, MCF-10A, indicating the feasibility of such a combinational treatment ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two mitogens were used to evaluate the immunomodulatory effects of the Imuno TF ® : LPS and Con A. Both LPS and Con A are widely used in in vitro and in vivo tests to assess the ability of cells to secrete various types of cytokines [29][30][31].…”
Section: Discussionmentioning
confidence: 99%